Association of interleukin gene polymorphism and clinical variables with external apical root resorption after initial stage of orthodontic treatment among Malay population - Nowrin, Shifat A (2021)
Orthodontic treatment brings numerous benefits and in most cases, the benefits outweigh the possible disadvantages. External apical root resorption (EARR) is a common adverse phenomenon associated with orthodontic treatment. It can be caused by some mechanical factors such as heavy retraction force, extrusion-intrusion or prolonged treatment duration. For biological factors, a genetic susceptibility such as polymorphisms in the interleukin-1 (IL-1) gene cluster have been implicated to increase the risk of EARR. Therefore, this study investigated the association of IL-1A, IL-1B and IL-1RN gene polymorphisms and EARR after finishing the initial (levelling and alignment) stage of orthodontic treatment. A total of 44 subjects (mean age 21.79 ± 3.83 years) who were undergoing orthodontic treatment with two different types of bracket system (conventional and self-ligating) were involved in this current study. Buccal cell swab was taken for genotyping and all subjects were genotyped by using polymerase chain reaction - restriction fragment length polymorphism (PCR-RFLP) for IL-1A and IL-1B genes and conventional PCR for IL-1RN gene. EARR in patients recruited for this study were measured from the cone beam computed tomography (CBCT) radiographs that were taken at the beginning of orthodontic procedures and after finishing the initial stage of orthodontic treatment. Intra-class correlation (ICC) and kappa test were then performed to ascertain the reliability of these EARR measurements and genotypes identification, respectively. Descriptive statistics were used for summarising the absolute and relative frequency of EARR in each anterior tooth. The EARR of contralateral and ipsilateral tooth was then compared using the Wilcoxon test. Meanwhile, Mann-Whitney test was performed to compare the EARR of two independent groups; gender, bracket system, skeletal classification and EARR versus control group. Binary logistic regression was used to assess interference from clinical confounding factors such as age, treatment modalities, sex, treatment duration and skeletal relationship. The distribution of genotypes and the allelic frequency of IL- 1A, IL-1B and IL-1RN gene polymorphisms in the subjects of both EARR and control group was analysed using Chi-square test. Univariate and multivariate logistic regression were used to identify the genetic association with EARR in orthodontic treatment. Results of ICC and kappa test showed strong correlations between interexaminer and intra-examiner in regards to EARR measurements and genotypes identification. The outcome of descriptive statistics analysis showed that a total of 96.9% of all anterior teeth manifested the root resorption after initial stage of the treatment. A total of 9.7% of the anterior teeth among all subjects possessed EARR of ≥2 mm after the initial stage of treatment. Wilcoxon test showed no statistical difference between the EARR of left and right side. However, right lateral incisor showed a significant difference when compared to the ipsilateral tooth. Mann-Whitney test did not show any significant differences between gender and between bracket system of EARR measurements. It was noted that lower left canine displayed increased EARR in Class I skeletal relation than the Class II skeletal relation. Moreover, it was also noted that right lateral incisors, lower left central incisor and canines possessed greater EARR resorptions of ≥2 mm than the control group (EARR <2 mm). Chisquare and logistic regression analyses within this study cohort showed no significant association between gene polymorphisms and EARR indicated that IL-1A, IL-1B and IL-1RN gene polymorphisms did not directly contribute to predisposition of EARR. The potential risk factors for EARR during orthodontic treatment is not associated with the IL-1A, IL-1B and IL-1RN gene in this study population.